2018
DOI: 10.2136/vzj2017.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

Soil Hydraulic Modeling Outcomes with Four Parameterization Methods: Comparing Soil Description and Inverse Estimation Approaches

Abstract: Different methods for parameterizing soil hydraulic models can lead to substantially varied predictions of soil-plant-atmosphere water fluxes. This study investigated, for a heterogeneous stony soil, four methods of soil hydraulic parameterization: (i) use of a pedotransfer function with a four-layer soil profile based on detailed soil physical and textural description; (ii) use of a pedotransfer function with a single-layer soil description; (iii) inverse estimation from soil moisture data; and (iv) inverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Winter precipitation appears to replenish water bound in both shallow and deeper soil. These results are in general agreement with lysimeter and eddy covariance studies conducted in the Canterbury region of New Zealand by Duncan, Srinivasan, and McMillan () and Graham, Srinivasan, Faulkner, and Carrick (, in press). Those studies showed that the majority of groundwater recharge takes place after a succession of winter rainfall events and that the majority of summer rainfall is evaporated or transpired during summer months.…”
Section: Discussionsupporting
confidence: 91%
“…Winter precipitation appears to replenish water bound in both shallow and deeper soil. These results are in general agreement with lysimeter and eddy covariance studies conducted in the Canterbury region of New Zealand by Duncan, Srinivasan, and McMillan () and Graham, Srinivasan, Faulkner, and Carrick (, in press). Those studies showed that the majority of groundwater recharge takes place after a succession of winter rainfall events and that the majority of summer rainfall is evaporated or transpired during summer months.…”
Section: Discussionsupporting
confidence: 91%
“…The simulation of water fluxes depends on the proper calibration of soil hydraulic properties (retention and conductivity) and is crucial for consistently simulating the vertical percolation rates under shallow groundwater conditions (Wessolek et al, 2008), such as in GEB. A study comparing four parametrization methods showed that the inverse calibration based on field soil moisture data implemented in the HYDRUS-1D model provided the best water flux predictions (Graham et al, 2018). Therefore, HYDRUS-1D was used in this study for calculating the matric-potentialdependent soil water retention [i.e., θ(h)] and hydraulic conductivity [i.e., K(h)] through the Mualem-van Genuchten soil hydraulic model (van Genuchten, 1980), including the option of air-entry detailed by Vogel et al (2000) (Equations 7-12):…”
Section: Soil Hydrological Modelling and Estimation Of Soil Hydraulic Parametersmentioning
confidence: 99%
“…The vertical percolation rate from the numerical simulation of the vadose zone is often considered as a proxy of groundwater recharge (Mathias et al., 2017). The simulation of these groundwater fluxes, however, come with the necessity of the proper calibration of some soil hydraulic parameters by means of soil moisture observations (Graham et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Both soil heterogeneity at different scales, from millimeters to kilometers, and the large amount of required data restrict the use of pedotransfer functions for the determination of SHPs and especially the soil water retention function [θ( h )] (Graham et al, 2018). Methods to measure SHPs, including pressure plates and in situ techniques like internal drainage experiments, are commonly laborious and costly.…”
mentioning
confidence: 99%
“…Direct measurement of K(h) is laborious, therefore K(h) is most commonly indirectly derived by using the measured saturated hydraulic conductivity, the q(h) function, and an empirical parameter related to tortuosity and connectivity, which, in its turn, exhibits a very large spatial variability (Durner et al, 1999). Consequently, any method to directly quantify K(h) represents an improvement of modeling quality, but this is predominantly neglected (Weninger et al, 2018;Weller et al, 2011). Both soil heterogeneity at different scales, from millimeters to kilometers, and the large amount of required data restrict the use of pedotransfer functions for the determination of SHPs and especially the soil water retention function [q(h)] (Graham et al, 2018). Methods to measure SHPs, including pressure plates and in situ techniques like internal drainage experiments, are commonly laborious and costly.…”
mentioning
confidence: 99%